Extracellular Vesicles from Adipose-Derived Mesenchymal Stem/Stromal Cells Accelerate Migration and Activate AKT Pathway in Human Keratinocytes and Fibroblasts Independently of miR-205 Activity - Andrea da Fonseca Ferreira; Pricila da Silva Cunha; Virgínia Mendes Carregal; Priscila de Cássia da Silva; Marcelo Coutinho de Miranda; Marianna Kunrath-Lima; Mariane Izabella Abreu de Melo; Camila Cristina Fraga Faraco; Joana Lobato Barbosa; Frédéric Frezard; Vivian Resende; Michele Angela Rodrigues; et al. (Hindawi Limited, 2017)
Mesenchymal stem/stromal cells (MSCs) are promising tools in cell therapy. They secrete extracellular vesicles (EVs) that carry different classes of molecules that can promote skin repair, but the mechanisms are poorly understood. Skin wound healing is a complex process that requires the activity of several signaling pathways and cell types, including keratinocytes and fibroblasts. In this study, we explored whether adipose tissue MSC-derived EVs could accelerate migration and proliferation of keratinocytes and fibroblasts, activate the AKT pathway, and promote wound healing in vivo. Furthermore, we evaluated if EV effects are miR-205 dependent. We found that MSC EVs had an average diameter of 135 nm. Keratinocytes and fibroblasts exposed to EVs exhibited higher levels of proliferation, migration, and AKT activation. Topical administration of EVs accelerated skin wound closure. Knockdown of miR-205 decreased AKT phosphorylation in fibroblasts and keratinocytes, whereas migration was decreased only in keratinocytes. Moreover, knockdown of miR-205 failed to inhibit AKT phosphorylation in fibroblasts and keratinocytes exposed to EVs. About the mechanism of EV effects, we found that incubation with EVs prevented inhibition of AKT activation by miR-205 knockdown, suggesting that EVs activate AKT independently of miR-205. In conclusion, we demonstrated that EVs are a promising tool for wound healing.